Beyond realism and postmordernism - Chatfield, T; Thomas Edward Francis Chatfield (2007)
﻿ This thesis evaluates and re-evaluates the relationship between the works of Philip Larkin, Kingsley Amis and Martin Amis through a detailed examination of their published works, and attempts to locate this relationship in the context of the central moral uncertainties of post-1945 British fiction. Most previous critical studies of these authors have tended to discuss the relationship between Kingsley Amis and Martin Amis in terms of an opposition between the father's realism and the son's postmodernism, and have debated Philip Larkin's influence upon Martin Amis only tangentially. Against this trend, this thesis argues that these three authors share a commitment to literature as a public, moral act, and, in particular, that their works share the intention of articulating a number of closely related secular 'human values' which map out a potential post-Christian morality in British society. The thesis also examines a common tension within their oeuvres inimical to such hopes - the fear that the possibilities of rational self-scrutiny and of becoming 'less deceived' have been discredited by the history of the twentieth century, and that this history instead evidences the dominance of irrational and self-destructive tendencies in the human. These fears, it is further claimed, are implicated in the works of all three authors in a tendency towards the construction of Edenic myths, deterministic simplifications, and despairing devaluations of the value of human life. Overall, this thesis makes the case for the significance of the common concerns of Martin Amis, Kingsley Amis and Philip Larkin's works in the context of contemporary literary studies: their efforts to create in art an unpretentiously 'public space' for the address of burning moral and existential issues, and their unresolved struggles with the question of what it might mean to live a good life in a society which no longer possesses religion as a common moral language.